Penerapan Model Pembelajaran Numbered Head Together (NHT) Diintegrasikan dengan Mata Pelajaran PAI dalam Meningkatkan Belajar Siswa di SMK Kreatif Hasbullah Bahrul Ulum Tambakberas Jombang - Ulfa, Maria; Chotimah, Chusnul; Zakariyah, Zakariyah (YASIN, 2025)
This study aims to improve students' interest and learning outcomes in Islamic Religious Education (PAI) through the implementation of the Numbered Heads Together (NHT) learning model. A descriptive qualitative method was employed, focusing on 10th-grade students at Hasbullah Creative Vocational School, Tambakberas Jombang. Data were collected through interviews, observations, and documentation, and analyzed inductively. The findings reveal that applying the NHT model effectively enhances student engagement, strengthens material understanding, and creates an interactive and enjoyable learning environment. By utilizing group discussions, students become more active, confident, and capable of deeply understanding concepts. This model also fosters effective teamwork through the distribution of individual responsibilities within groups. Additionally, the application of NHT significantly improved students’ average scores and provided a meaningful learning experience. The study recommends the NHT model as an alternative interactive teaching method in PAI to improve learning outcomes and develop collaborative character among students.